EDITORIAL NOTE Vol. 60 (08/2024) RA’E GA – THE GEOGRAPHIC SPACE UNDER ANALYSIS - Breunig, Fábio Marcelo (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
RA’E GA – THE GEOGRAPHIC SPACE UNDER ANALYSIS is pleased to present to the national and international scientific community the second volume of 2024 (V.60 – 08/2024 - DOI: http://dx.doi.org/10.5380/raega.v60i0.95325), which encompasses articles covering various topics related to Geographic knowledge and other areas of scientific expertise. This edition of the Journal maintains the publication flow in English and Portuguese. This change aimed to preserve the Papers construction structure of the texts and increase access for different readers. RA’E GA extends its gratitude to the authors, the editorial team, section editors, and reviewers, especially those who contributed to this volume (Reviewers ROBERTO GOERL, MÁRCIA SILVA, ZENO CROCETTI, EUGÊNIA PEREIRA, EDNER BAUMHARDT, ANDRESSA FERLA, TARIK CUCHI, CLÁUDIA VALE, MARCOS TORRES, FABIO MARCELO BREUNIG, ELIAS F BERRA; TONY SAMPAIO, APARECIDO ANDRADE, ISABEL PEDRON, FERNANDO PASINI, LIDIA KUHN, VANDOIR BOURSCHEIDT, RENATO BEPPLER SPOHR, ROMÁRIO TRENTIN, INOCENCIO BORGES NETO, ARTHUR SANTOS, LEILA LIMBERGER, ISADORA HADDAD, ALEXANDRE UHLMANN, CLÁUDIA VALE), as well as the Program for Support of Periodical Scientific Publications at UFPR. All these activities are crucial for the advancement of Brazilian scientific research and have been instrumental in ensuring the quality of this current volume.